Konsep Sabar dan Shalat Perspektif Tafsir Al-Misbah Sebagai Self-Healing - Anistiawati Bulandari Qasanah; Umar Faruq Thohir (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2024)
Modernization has changed the lives of many social communities resulting in many social problems such as mental damage. Efforts to cure mental health religiously are by applying the concept of 'patience and prayer', both in religious and cultural contexts. In everyday life this concept is also widely used by people when facing various psychological problems, for example facing stressful situations, facing problems, or calamities or when experiencing angry emotional conditions. This research uses a qualitative approach and the type of research is library research, which is an attempt to obtain data in the literature. By reviewing books by Quraish Shihab. The data analysis uses a descriptive-analytical approach whose sources are recorded, collected analyzed and then interpreted critically before being poured and implemented in an idea. In Tafsir al-Misbah it is explained that patience and prayer can help self-healing, both physically and psychologically which is also beneficial for life, namely in the form of peace of mind, a source of faith and tranquility, therapy for anxiety and solution giver and as amar ma'ruf nahi munkar.